Luaran Bayi Baru Lahir Pada Persalinan dengan Ketuban Pecah Dini di RS Wava Husada Kepanjen Malang - Asmara, Jana; Seftyandini, Nadia; Tarsikah, Tarsikah; Naimah, Naimah (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2022)
One of the causes of newborn death due to complications in childbirth is premature rupture of membranes (PROM). Premature rupture of membranes can cause several complications in infants including prematurity, asphyxia, hypoxia, neonatal infection, morbidity and mortality. This study aims to identify the outcome of newborns with premature rupture of membranes at Wava Husada Hospital Kepanjen Malang. The research design used is descriptive quantitative with a retrospective approach. The sampling technique used is total sampling with a sample size of 150 respondents. The research variable is the description of newborns in mothers giving birth with premature rupture of membranes. The instruments used are medical records and checklists. The analysis used is descriptive analysis. The results showed that almost all of the babies born at term (83.3%), had normal baby weight (86.7%), had mild asphyxia (99.3%), none of the babies had newborn infections (100 %), premature rupture of membranes >12 hours (51.3%,) delivery by caesarean section (88.7%), and mothers who experienced PROM without other complications (74%). Pregnant women are expected to increase knowledge about PROM, prevention efforts, complications caused by PROM, and other conditions that aggravate these complications. Keywords: Newborn Baby, Premature Rupture of Membranes